MDPF: Minimum Distance Packet Forwarding for Search Applications in Mobile Ad Hoc Networks - Artail, Hassan (2009)
This paper introduces a message forwarding algorithm for search applications within mobile ad hoc networks that is based on the concept of selecting the nearest node from a set of designated nodes. The algorithm, which is called Minimum Distance Packet Forwarding (MDPF), uses routing information to select the node with the minimum distance. The goal of the proposed algorithm is to minimize the average number of hops taken to reach the node that holds the desired data. Numerical analysis and experimental evaluations using the network simulation software ns2 were performed to derive the lower and upper bounds of the confidence interval for the mean hop count between the source node of the data request, on one hand, and the node that holds the desired data and the last node in the set of search nodes, on the other hand. In the experimental evaluation, the performance of MDPF was compared to that of Random Packet Forwarding (RPF) and Minimal Spanning Tree Forwarding (MSTF). The results agreed with the numerical analysis results and demonstrated that MDPF offers significant hop count savings and smaller delays when compared to RPF and MSTF.